2020
DOI: 10.3892/ol.2020.12292
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits epithelial‑mesenchymal transition of oral squamous cell carcinoma via the mTOR/HIF‑1α/PKM2/STAT3 pathway

Abstract: Epithelial-mesenchymal transition (EMT) serves an important role in the formation and development of various types of cancer, including oral squamous cell carcinoma (OSCC). Metformin, used for treating type 2 diabetes, has been revealed to exert an anticancer effect in various types of cancer, including liver, breast and colorectal cancer. However, its role in the EMT of OSCC has been rarely reported. Therefore, the present study aimed to investigate the effects of metformin on EMT and to identify its underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
(38 reference statements)
0
15
0
1
Order By: Relevance
“…Melatonin is a well-recognized suppressor of HIF-1α under a number of experimental conditions [65][66][67]. While Fig.…”
Section: Melatonin/hif1α Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin is a well-recognized suppressor of HIF-1α under a number of experimental conditions [65][66][67]. While Fig.…”
Section: Melatonin/hif1α Interactionsmentioning
confidence: 99%
“…Melatonin is a well-recognized suppressor of HIF-1α under a number of experimental conditions [ 65 67 ]. While the mechanism of that suppression is not specifically known [ 68 ], it may be the result of its direct inhibition of the cytosolic oxygen sensor or related to the potent antioxidant activity of the molecule which removes the agents that stabilize HIF-1α, i.e., ROS [ 69 ].…”
Section: Melatonin/hif1α Interactionsmentioning
confidence: 99%
“…Based on the facts described above, we can conclude that CVB may exert its anti-ccRCC functions by reducing the expression of Snail. Multiple biological signalling cascades participate in the regulation of Snail, including the PI3K/AKT signalling pathway, JAK/STAT3 signalling pathway and MAPK signalling pathway, and these pathways are expected to be attractive therapeutic targets for ccRCC [33][34][35]. In our study, all of these cascades, without exception, were remarkably inhibited by CVB, indicating that the suppression of AKT/STAT3/ MAPK-Snail signalling networks may be the mechanism by which CVB exerts its powerful therapeutic effects on ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Hallmarks of the EMT include destabilization of adherens junctions, tight junctions and desmosomes, critical structures necessary to maintain epithelial integrity, as well as up regulation of vimentin and α-smooth muscle actin (Lamouille et al, 2014). Recent studies indicated that metformin inhibits EMT in cells derived from different types of cancer including gastric, colon, thyroid, breast, oral and prostate (Esparza-Lopez et al, 2019;Han et al, 2015;Valaee et al, 2017;Wang et al, 2018a;Yin et al, 2021;Zhang and Wang, 2019;Zhang et al, 2014). Several mechanisms had been proposed to explain the inhibitory effect of metformin upon EMT such as down-regulation of transcription factors (SNAIL, TWIST and ZEB), inhibition of PI3K/AKT/mTOR, MAPK, TGFβ, IL-6 and IL-8 signaling and up regulation of miR-381 and miR-200c (Chen et al, 2020).…”
Section: Metformin E-cadherin Fak and Metforminmentioning
confidence: 99%